Coastal vertical wind lidar measurements of horizontal wind speed and wind direction from 40 to 500 m at Norderney island, German Bight, North Sea, Germany - Thomas Rausch; Beatriz Cañadillas; Astrid Lampert (PANGAEA, 2023)
A profiling ground-based Wind-LiDAR system, Windcube WLS8, developed by Leosphere (now Vaisala), was installed at the German Weather Service (DWD) (N 53° 42.75 extquotesingle, E 007° 09.13 extquotesingle, at Norderney Island) on 8 September 2019 to acquire coastal wind profiles as part of the research project X-Wakes. The island of Norderney (dimension of 14 km x 2.5 km) is one of the East Frisian Islands and lies only a few kilometres from the German North Sea coast. The DWD site is located at an altitude of 7 m above sea level. No obstacles interfere with the lidar measurement. The Wind-LiDAR provided the vertical profiles of the wind speed components, measured by means of the Doppler Beam Swinging technique. Four lines of sight are sequentially scanned by a 1.54 μm pulsed fiber laser to perform the geometrical computation of the 3D wind vector components. From the raw data, the average horizontal wind speed and wind direction is calculated routinely for intervals of 10 min. The wind speed and direction, retrieved from the lidar system, are available at 25 height levels between 40 m and 500 m, with a vertical resolution of 10 m up to 100 m, 20 m up to 400 m, and 50 m up to 500 m. Data gaps are mainly caused by low clouds and fog, which cannot be penetrated by the laser pulses.